Analysis of the Effect of Cutting Depth in the Thread-Making Process on Fatigue Testing Using a CNC Gedee Weiler Learn Turn - Mhd Bagas Alfian Rizky; Aljufri Aljufri; Suryadi; Muhammad Nuzan Rizki; Ferri Safriwardy; Rahmatsyah Maksum Ramsi (Malikussaleh Journal of Mechanical Science and Technology, 2026)
A thread is an essential element of a bolt that functions as both a fastener and a force-transmitting component, and therefore must be able to withstand both static and dynamic loads. In practical applications, threads are frequently subjected to repeated loading, which can potentially lead to failure due to material fatigue. This study aims to analyze the effect of thread depth variation on the fatigue resistance of AISI 1045 steel processed using a CNC Gedee Weiler Learn Turn machine. The thread depth variations used were 0.4 mm, 0.6 mm, and 0.8 mm. The testing method was carried out using a rotary bending fatigue machine until the specimen fractured, after which the number of cycles to failure and the resulting bending stress were calculated. The test results show that the greater the thread depth, the higher the bending stress experienced by the specimen, namely 227.7 MPa at a depth of 0.4 mm, 253.8 MPa at a depth of 0.6 mm, and 284.3 MPa at a depth of 0.8 mm. However, an increase in thread depth resulted in a decrease in the number of cycles to failure. The specimen with a 0.4 mm thread depth exhibited the most optimal and highest fatigue life value, at 5,127.54 cycles, whereas the specimen with a 0.8 mm thread depth achieved the most optimal fatigue life of only 2,603.04 cycles. These findings indicate that a shallower thread depth provides better fatigue resistance in AISI 1045 steel.